Sola Scriptura: Strengths and Challenges. Issue 3 (September 2016) - Jacobson, Diane
Abstract: When Luther's notion of sola Scriptura is nuanced and properly understood, it is engaging and true in its assertions. However, in today's world, the use of the expression sola Scriptura may be more problematic than helpful. This point is argued for three reasons: Lutheran relationships with Catholics; the rise of American fundamentalism; and the parallel rise of "nones, " that largely young group of agnostics (sometimes atheists) not affiliated with any organized religion. By considering these issues, we can see how the notion still has relevance for theology and for the broader church, and how this notion helps us to preach, teach, and live the gospel in this time and place.